Exploring the land-use futures related to reindeer herding in Finland through “wild logic” scenarios - Simo Sarkki; Sirpa Rasmus; Joachim Otto Habeck; Heidrun Matthes; Mia Pihlajamäki; Jussi T. Eronen (Journal of Land Use Science)
Anticipating futures can inform today’s decisions. However, existing scenario approaches need systemic methods to diversify the established storylines and to incorporate surprises. We propose a ‘wild logic’ scenario method, which is informed by participatory work and combines logic from exploratory scenarios with assumptions on governance modes. We apply the proposed method to a case of reindeer herding in Finland, building on Shared Socioeconomic Pathway (SSP) storylines and three assumptions on hierarchical, collaborative and affirmative governance. Our main result is an SSP – governance assumption matrix consisting of 10 storylines with divergent implications on land use and social equity for reindeer herders. Our approach was able to produce novel aspects that expand on existing scenario work in the Arctic, especially by addressing affirmative governance. The method is also applicable beyond the Arctic contexts, and can be combined with other than SSP exploratory scenarios, and with other than governance-related assumptions.